2018
DOI: 10.1016/j.cmi.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Admission lactate predicts poor prognosis independently of the CRB/CURB-65 scores in community-acquired pneumonia

Abstract: Admission lactate levels significantly improved the prognostic value of the CRB/CURB-65 scores in CAP patients. Lactate may therefore be considered a rapid, cheap and broadly available additional criterion for the assessment of risk in patients with CAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
3
32
0
1
Order By: Relevance
“…It should be noted that during the study period, all scores were being used in clinical practice, except for qSOFA, and this may have had an impact on the decision-making process when a patient was admitted to ICU. Our ICU admission rate is lower than that seen in studies performed outside the UK7 15 28; however, it is in keeping with the BTS pneumonia audit 27. This is likely to be due to inclusion of patients with treatment limitations; we choose to include patients with treatment limitations to enable application of these scores to all patients admitted.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It should be noted that during the study period, all scores were being used in clinical practice, except for qSOFA, and this may have had an impact on the decision-making process when a patient was admitted to ICU. Our ICU admission rate is lower than that seen in studies performed outside the UK7 15 28; however, it is in keeping with the BTS pneumonia audit 27. This is likely to be due to inclusion of patients with treatment limitations; we choose to include patients with treatment limitations to enable application of these scores to all patients admitted.…”
Section: Discussionsupporting
confidence: 84%
“…It is associated with significant mortality2 and frequently leads to sepsis3 4 with mortality rates rising to 30% 5. Early identification of patients with severe CAP enables modification of management strategies and improves outcomes for patients 6–8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency Medicine International mortality and ICU admission in pneumonia patients in ED, while results indicated that lactate is superior to CURB65 in predicting mortality, hospitalization, and intensive care unit (ICU) admission and lactate-CURB65 combination improves the predictive value of single CURB65 [10]. A similar study by Frenzen and colleagues concluded that admission lactate levels significantly improved the prognostic value (need for mechanical ventilation, vasopressors, ICU admission, or hospital mortality) of CRB/CURB65 scores in CAP patients with an optimal cutoff value of 1.8 mmol/L [23]. Song et al enrolled 443 patients with CAP in ED, and results showed that the AUROC of qSOFA and SOFA for prediction of mortality was 0.720 and 0.845, while the combination of qSOFA and lactate was not significantly different from SOFA [24].…”
Section: Discussionmentioning
confidence: 95%
“…Hyperlactataemia is an independent predictor of mortality in both pneumonia and sepsis 71. Much evidence now supports the view that hyperlactataemia is not only due to tissue hypoxia or anaerobic glycolysis but also due to increased aerobic glycolysis (the conversion of pyruvate to lactate to generate ATP in the presence of oxygen).…”
Section: Host Immune System At the Extremes Of Agementioning
confidence: 95%